2018
DOI: 10.1111/odi.12991
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of immune checkpoints in oral squamous cell carcinoma

Abstract: Background Despite the importance of immune checkpoints in immunotherapy, the prognostic value of these molecules remains controversial in oral squamous cell carcinoma (OSCC). We performed a systematic review to investigate the prognostic significance of the immune checkpoints in OSCC. Materials A systematic search was conducted in Ovid Medline, Scopus and Cochrane libraries, and all studies that evaluated the prognostic significance of immune checkpoints in OSCC were systematically retrieved. Results Twelve i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 37 publications
1
35
0
Order By: Relevance
“…Overexpression of IDO1 is considered one mechanism of cancer cell immune evasion and thus its inhibition may enhance the host antitumor immune response. Melanoma patients overexpressing IDO1 have been noted to respond favorably to PD‐L1 inhibitors . Overexpression of PD‐L1, IDO1, higher rates of tumor infiltrating CD8 T lymphocytes, and enrichment of interferon gamma gene signatures have all been shown to be correlated with better response to PD1/PD‐L1 pathway inhibition …”
Section: Implications For Immunotherapymentioning
confidence: 99%
“…Overexpression of IDO1 is considered one mechanism of cancer cell immune evasion and thus its inhibition may enhance the host antitumor immune response. Melanoma patients overexpressing IDO1 have been noted to respond favorably to PD‐L1 inhibitors . Overexpression of PD‐L1, IDO1, higher rates of tumor infiltrating CD8 T lymphocytes, and enrichment of interferon gamma gene signatures have all been shown to be correlated with better response to PD1/PD‐L1 pathway inhibition …”
Section: Implications For Immunotherapymentioning
confidence: 99%
“…13 In addition, several authors found B7-H3 overexpression associated with advanced tumor stage, increased proliferation and poor patient outcome in breast, endometrial, pancreatic, cervical, ovarian, oral squamous cell, cholangiocellular carcinoma and lung cancer. [14][15][16][17][18][19][20][21] Also nonepithelial tumors such as melanoma, 22 osteosarcoma 23 or gliomas 24 show B7-H3 overexpression. Others described associations between high B7-H3 expression and favorable tumor course in pancreatic 25 and gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
“…3 Despite the advance in therapeutic strategies, such as chemotherapy and surgery, the prognosis of OSCC is still poor, and it has no significant improvement in the overall survival rate of OSCC patients. 4,5 Hence, it is important to verify novel candidate molecules and more efficacious therapeutic approaches for OSCC. Ubiquitin-proteasome system is an essential pathway for protein degradation, consists by abnormal and short-lived protein, and located in the nucleus and cytoplasm.…”
Section: Introductionmentioning
confidence: 99%